THE IMPACT OF HYPNOTEACHING LEARNING METHODS ON STUDENTS’ BIOLOGY ACHIEVEMENT IN MIA GRADE IX SENIOR HIGH SCHOOL 1 GOWA - Ulfa Alfiani Ahmad; Hilmi Hambali; Anisa Anisa (Jurnal Riset dan Inovasi Pembelajaran, 2021)
This study aims to determine the learning outcomes of MIA XI grade students of SMA Negeri 1 Gowa on Biology subjects taught using hypnoteaching learning methods and Quasi experimental research type with nonequivalent control group design. The research instruments used were tests, questionnaires, and observation sheets. Data processing is done by descriptive statistical analysis and inferential statistical analysis. The variables studied in this study were the application of hypnoteaching learning methods and learning outcomes. The results of the data analysis showed the application of hypnoteaching learning methods to student learning outcomes. This is indicated by the difference between student learning outcomes taught by using the Hypnoteaching learning method and student learning outcomes not taught by using the Hypnoteaching learning method in the control class and the experimental class. This is reviewed based on a comparison of the final learning outcomes of the experimental class, namely an increase in the average score of 33.74 to an average score of 87.60. Based on the data obtained it can be concluded that the Hypnoteaching learning method can improve student learning outcomes in Biology subjects. The results of inferential statistical analysis using covariance analysis obtained a Sig. calculate value (0.000) <α (0.05) which shows that H0is rejected and H1 is accepted. Thus, it can be stated that there is a very significant difference between student learning outcomes in the control class and the experimental class.